MITIGASI EMISI GAS RUMAH KACA - Jatmiko Wahyudi (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2018)
ENGLISHClimate change becomes one of the most intensely critical issues over the last decade until today. Eventhough greenhouse gases (GHG) occur naturally in the atmosphere, anthropogenic is mainly responsible for increasing the greenhouse gases emission causing global warming/climate change. Actually, these gases play important roles for regulating the temperature of earth and earth atmosphere so that suitable for living things. Carbon dioxide (CO2) occupies more than half (76.7%) of the total GHG emission and energy supply becomes the most contributor of GHG emissions among other sectors. Climate change could lead to many environmental problems i.e., drought, floods, rising sea level, shifting weather pattern, greater variability of rainfall etc. For archipelagic country like Indonesia, the resulting sea level rise would give impact on inundation of coastal areas and increased loss of coastal habitats and ecosystem. The mitigation of GHG emissions is an option to reduce the intesity of global warming. As a part of global community, The government of Indonesia has a commitment to reduce the country’s GHG emissions by 26% with national resources or up to 41% with international support from a business-as-usual baseline by 2020. INDONESIAPemanasan global menjadi salah satu isu terpenting pada abad terakhir ini. Walaupun secara alami telah ada di atmosfer bumi, aktivitas manusia diyakini memberikan kontribusi yang signifikan terhadap peningkatan emisi gas rumah kaca (GRK) penyebab pemanasan global. Karbondioksida berkontribusi sebesar 76,7% dari total emisi GRK dan sektor penyediaan energi merupakan sektor yang menghasilkan emisi GRK terbesar dibandingkan sektor-sektor lain. Perubahan iklim menyebabkan terjadinya kekeringan, banjir, kenaikan muka air laut, perubahan cuaca, ketidakmenentuan pola curah hujan dan lain-lain. Bagi negara kepulauan seperti Indonesia, kenaikan muka air laut akan menyebabkan tenggelamnya kawasan pesisir dan meningkatkan hilangnya habitat dan ekosistem kawasan pesisir. Mitigasi emisi gas rumah kaca merupakan salah satu opsi untuk mengurangi semakin meningkatnya pemanasan global. Sebagai dukungan terhadap upaya dunia untuk mengurangi emisi GRK, Pemerintah Indonesia berkomitmen untuk menurunkan emisi GRK sebesar 26% dengan usaha sendiri dan 41% dengan bantuan internasional pada tahun 2020 dari kondisi tanpa adanya rencana aksi.